2008
DOI: 10.1177/070674370805300905
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Quality of Life in Psychiatric Patients: Diagnosis and Illness-Specific Profiles

Abstract: Objective:In accordance with the definition of health by the World Health Organization, outcome measures beyond mere syndromic recovery, such as quality of life ratings, would aid psychiatric practice and research. This is the first study of psychiatric diagnosis and illness stage specific profiles of subjective quality of life (SQOL) impairment.Method: Patients (n = 150) hospitalized at the Prague Psychiatric Center rated their SQOL using the Schwartz Outcome Scale at admission and discharge. Severity of illn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
4
19
1
Order By: Relevance
“…The data are not in agreement with the findings of previous studies (e.g. Goppoldova et al 2008;Hodgson et al 2007) which suggest changes in the psychiatric patients' QoL depending on their diagnosis. These results can be explained by the fact that all participants are patients of the Psychosocial Rehabilitation Service-a service that aims to promote a better QoL through occupational therapy, psychological counselling, nursing and psychiatric careand, consequently, it appears that changes to the patients' QoL may have been promoted to the point where it has stabilised at a regular level-regardless of their diagnosis-justifying the absence of differences between groups.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The data are not in agreement with the findings of previous studies (e.g. Goppoldova et al 2008;Hodgson et al 2007) which suggest changes in the psychiatric patients' QoL depending on their diagnosis. These results can be explained by the fact that all participants are patients of the Psychosocial Rehabilitation Service-a service that aims to promote a better QoL through occupational therapy, psychological counselling, nursing and psychiatric careand, consequently, it appears that changes to the patients' QoL may have been promoted to the point where it has stabilised at a regular level-regardless of their diagnosis-justifying the absence of differences between groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Maslow (1998) stipulates the need for self-actualisation of the human being, in the way in which he or she understands and interacts with reality. This is in agreement with Gorsuch (2002), who states that ''spirituality is the quest for understanding ourselves in relationship to our view of ultimate reality, and to live in accordance with that understanding'' (p. 8). Note the absence of the concept of the divine from this definition, which was purposefully omitted; a purely ontological vision is emphasised rather than a theological perspective.…”
Section: Spirituality and Mental Healthsupporting
confidence: 88%
See 1 more Smart Citation
“…Because the HRQoL score was non-normally distributed, only the EQ-VAS was used as the dependent variable, and the following candidate factors were used as independent variables: age, gender, duration of illness, duration of hospitalisation, GAF at admission, use of GAF change, SUMD-J, legal status of admission, the occurrence of restraint, seclusion or forced mediation and perceived coercion. We performed separate analyses for patients with and without a diagnosis of ICD-10 F2 because it was suggested that illness-specific mechanisms are associated with QoL (Goppoldova et al, 2008). The model was accepted if the maximum variance inflation factor (VIF) value was o 5.…”
Section: Discussionmentioning
confidence: 99%
“…We carefully analyzed the influence of social factors on HrQoL in APS and identified level of education as one of the independent determinants of the HrQoL. This may reflect insight and expectations of patients, which are known to have influence on quality of life in other chronic diseases [35,36] . Future studies on HrQoL in APS should integrate evaluation of insight (e.g.…”
Section: Discussionmentioning
confidence: 99%